Morphometric-Based Investigation of Genetic Diversity Among Mango (Mangifera indica L.) Populations in the Ecosystems of Lagos and Ogun States, Southwestern Nigeria - Moses Sunday Afariogun; Omeyiza Micheal Ibrahim (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Mango (Mangifera indica L.), regarded as the "king of fruits," holds a critical position in the Nigerian diet, ranking second only to banana in terms of consumption. This study was conducted to assess the morphometric diversity of mango in Lagos and Ogun States, located in Southwest Nigeria. A total of forty mango varieties were analyzed, comprising twenty accessions collected from different locations within each state. Morphological evaluation was based on the International Plant Genetic Resources Institute (IPGRI) descriptors for mango. Both qualitative and quantitative morphological traits, including leaf, inflorescence, and fruit characteristics, were systematically assessed through field observations and laboratory analyses. Significant variability was recorded among the mango accessions, particularly in qualitative traits such as immature leaf color, leaf shape, inflorescence axis structure, flower color, flower type, fruit shape, fruit skin color, and fruit skin texture. The observed morphological diversity highlights the genetic richness present in the mango populations of the studied regions, offering valuable insights for future breeding and conservation programs.